Kawalan kualiti dengan carta kawalan purata bergerak berpemberat eksponen serta aplikasi indeks kebolehupayaan terhadap proses pembuatan blower armature - Firdaus Mohamad Hamzah , (Penerbit ukm, 2005)
This study is done on one of the products manufactured by a Japanese factory located in Bangi, Selangor. The main purpose of this study is to determine whether the production process is in control or not and to obtain the capability index for the manufacturing process of blower armature product. The quality attribute of the blower armature is the length measurement (in mm) in the process of commutator furnishing. In this study, several statistical methods such as histogram, normal probability plot, process capability index and exponential weighted moving average chart have been successfully used. The findings from the exponential weighted moving average chart show that the production process is out of control. The process capability index shows that the process involved has the potential of being capable in the future but this will not happen since the location of the process mean is not at the centre of the specification limits